A ANALYSIS OF THE NEED FOR DEVELOPMENT OF COMPUTER BASED TEST (CBT) ASSESSMENT BASED ON HIGH ORDER THINKING SKILL (HOTS) IN BIOLOGICAL LEARNING - Prihantini, Ria Setia; Masruhim, Muh Amir; Daniel, Daniel (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2020)
The purpose of this study was to obtain a description of the views and constraints faced by teachers and students in the field regarding the development of assessment instruments . This research is only limited to needs analysis research which is sourced from the results of initial observations and a review of the relevant literature. Researchers made observations in four schools, namely public senior high school4 Samarinda, public senior high school 6 Samarinda, public senior high school 15 Samarinda and public senior high school Samarinda. The data collection technique in this study used an analysis of the needs of teachers and students. The results of the observations were in the form of an instrument of teacher needs assessment which was analyzed using descriptive qualitative analysis. The researcher found that the development of assessment instruments Teachers have never done a Computer Based Test based on High Order Thinking in Biology learning because of the teacher's limited knowledge of computer-based exams, the teacher's limited time in making assessment instruments, limited facilities and infrastructure. Learners want assessments that are more attractive and efficient for them .